Daur Munazhamat al-Lughah al-‘Arabiyyah bi Indunisiya fi Da’mi al-Mu’allimin wa at-Thalabah - Ningsih, Kurnia; Zahasfan, Alvian Iqbal (Jurnal Internasional Pendidikan Bahasa Arab, 2024)
The objective of this article is to ascertain the function of Arabic organizations in the development of the competence of Arabic teachers and Arabic student universities. The implementation of distance learning through electronic learning has been significantly impacted by the Covid-19 pandemic. The data for this study was collected through interviews with all of the chiefs of Arabic organizations in Indonesia, utilizing the qualitative method. IMLA Indonesia, F-MGMP Bahasa Arab, ITHLA, and IMASASI are national Arabic organizations that are influential in the development and promotion of the complexities of Arabic teaching and learning in Indonesia. This is where Arab organizations are working diligently to coordinate virtual training, seminars, workshops, activities, treatments, and competitions to enhance the skills of Arabic language teachers and students, as well as to enhance their capacity to conduct effective and efficient distance learning. This research has demonstrated that the programs of IMLA Indonesia, F-MGMP Arabic, ITHLA, and IMASASI have the potential to enhance the quality of Arabic language education in Indonesia by providing competent solutions to the challenges of the Covid-19 era and the future of digital Arabic language learning.